The association between maternal tobacco smoking during pregnancy and the risk of attention-deficit/hyperactivity disorder (ADHD) in offspring: A systematic review and meta-analysis - Mahdi Mohammadian; Lusine G. Khachatryan; Filipp V. Vadiyan; Mostafa Maleki; Fatemeh Fatahian; Abdollah Mohammadian-Hafshejani (PLoS ONE, 2025)
Introduction Maternal tobacco smoking during pregnancy is a significant public health concern with potential long-lasting effects on child development. ADHD, a neurodevelopmental disorder characterized by inattention, hyperactivity, and impulsivity, may be influenced by prenatal nicotine exposure. This systematic review and meta-analysis examine the association between maternal tobacco smoking during pregnancy and the risk of ADHD in offspring. Methods Following PRISMA guidelines, we searched databases including PubMed, Web of Science, Cochrane Central, Embase, Scopus, CINAHL, LILACS, SciELO, Allied and Complementary Medicine Database (AMED), ERIC, CNKI, HTA Database, Dialnet, EBSCO, LENS, and Google Scholar for studies up to November 1, 2024. We included peer-reviewed studies reporting quantitative effect size estimates for the association between maternal tobacco smoking and ADHD. Study quality was assessed using the Newcastle-Ottawa Scale (NOS). Results We identified 2,981 articles and included 55 studies (4,016,522 participants) in the analysis. The meta-analysis showed a significant association between maternal tobacco smoking during pregnancy and increased risk of ADHD in offspring (pooled Odds Ratio (OR) = 1.71, 95% CI: 1.55-1.88; P < 0.001). Egger’s test indicated no publication bias (p = 0.204), but Begg’s test did (p = 0.042). By employing the trim and fill method, the revised OR was estimated to be 1.54 (95% CI: 1.40–1.70; P < 0.001). The OR were 2.37 (95% CI: 1.72–3.28; P < 0.001) in cross-sectional studies, 1.72 (95% CI: 1.49–2.00; P < 0.001) in case-control studies, and 1.53 (95% CI: 1.34–1.74; P < 0.001) in cohort studies. Meta-regression showed study design and study region significantly influenced heterogeneity (P < 0.10). Sensitivity and subgroup analyses confirmed the robustness of these findings. Conclusion This systematic review and meta-analysis demonstrate a significant association between maternal tobacco smoking during pregnancy and increased odds of ADHD in offspring. These findings highlight the need for prenatal care guidelines and tobacco smoking cessation programs for pregnant women to reduce ADHD risk and promote optimal neurodevelopmental outcomes. Future research should explore underlying mechanisms and potential confounders further.